2011
DOI: 10.1038/nature10454
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic priming by a secreted fungal effector

Abstract: Maize smut caused by the fungus Ustilago maydis is a widespread disease characterized by the development of large plant tumours. U. maydis is a biotrophic pathogen that requires living plant tissue for its development and establishes an intimate interaction zone between fungal hyphae and the plant plasma membrane. U. maydis actively suppresses plant defence responses by secreted protein effectors. Its effector repertoire comprises at least 386 genes mostly encoding proteins of unknown function and expressed ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
497
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 517 publications
(536 citation statements)
references
References 37 publications
8
497
2
1
Order By: Relevance
“…P. syringae type III effectors can alter the accumulation of chorismate-and Phe-derived metabolites (Jelenska et al, 2007;Zhou et al, 2011). U. maydis deploys effectors that suppress SA production (Djamei et al, 2011) and promote anthocyanin production (Tanaka et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…P. syringae type III effectors can alter the accumulation of chorismate-and Phe-derived metabolites (Jelenska et al, 2007;Zhou et al, 2011). U. maydis deploys effectors that suppress SA production (Djamei et al, 2011) and promote anthocyanin production (Tanaka et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work with Ustilago maydis showed that the fungal effector Cmu1 is a chorismate mutase that attenuates SA production in infected maize (Djamei et al, 2011). We hypothesized that WtsE, through its perturbation of phenolic metabolism, might similarly suppress SA accumulation.…”
Section: Metabolic Flux Through the Shikimate Pathway And Pal Activitmentioning
confidence: 99%
“…Delivery of effectors into host cells by eukaryotic pathogens has been demonstrated in several plant pathogen systems (7)(8)(9)(10)(11)(12), and, in some cases, fungal and oomycete host-cell translocation can occur in the absence of the pathogen (7,(12)(13)(14)(15)(16), suggesting that a hostencoded transport machinery is responsible for internalization of the effectors. Conserved short N-terminal motifs such as RXLR and LXLFLAK have been identified in oomycete-effector protein families (17), and they have been shown to be both necessary and sufficient for plant-cell entry (9,16,18).…”
mentioning
confidence: 99%
“…The basic criteria to identify candidate secreted effector proteins are: proteins with a signal peptide (within the initial 60 amino acids at the N-terminus), no trans-membrane domains, small size between 300 to 450 amino acids, and mostly species-specific [32,39,40]. These parameters were those used in the identification of putative P. brassicae effectors in the previously mentioned studies (Table 1).…”
Section: Where and How To Look For Effectors?mentioning
confidence: 99%